COMPARATIVE AND COMPETITIVE ADVANTAGES ANALYSIS OF CASSAVA, CASE IN SIMALUNGUN DISTRICT, NORTH SUMATERA PROVINCE, INDONESIA - Junnia Pramesthia Putri; S Suhartini; Nuhfil Hanani (Agricultural Socio-Economics Journal, 2019)
Abstract: This study aims to analyze the competitive advantage and comparative advantage of cassava in Simalungun Regency, North Sumatera Province, which will be focused on increasing the production more better and more diversified through the approach of cassava farming activities. This context, based on the demand side of cassava commodity that is feasible to be developed by increasing its production in order to influence the level of income that will be received by farmers. This paper is proposed to: (a) analysis of farming both financially and economically, (b) comparative and competitive analysis, (c) to formulate the interim policy assumption of both advantages. Result of Matrix Policy Analysis Method (PAM), indicating that both of these commodities has a comparative and competitive advantage, shown by the ratio of DRC and PCR less than 1. Calculation shows DRC for cassava equal to 0.259. PCR of cassava farming is 0.66. This value means that cassava farming in Simalungun district can be said to have superiority comparative and competitive advantage. In other words, cassava farming at more research sites more better to be produced domestically rather than imported.